2017
DOI: 10.32800/abc.2017.40.0193
|View full text |Cite
|
Sign up to set email alerts
|

Spring evaluation of three sampling methods to estimate family richness and abundance of arthropods in olive groves

Abstract: Spring evaluation of three sampling methods to estimate family richness and abundance of arthropods in olive groves.-The intensification and expansion of agriculture is currently one of the greatest threats to biodiversity worldwide. Olive groves are one of the most extensive and diverse agroecosystems in the Mediterranean region. However, the efficiency of the methods used to sample arthropods in olive crops remains unclear. We compared the effectiveness of pan traps, sweep net and bait traps used to sample a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…The differences in catches between YST and TST were evident in our study for almost all taxa captured over the two-year study period. Significant differences were observed in both seasons for several orders, indicating a natural preference towards yellow for taxa such as Diptera (Bekker et al, 2017), Homoptera (Castro et al, 2017), Hymenoptera (Thomson et al, 2004;Gullan and Cranston, 2005) and Thysanoptera (Thomson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in catches between YST and TST were evident in our study for almost all taxa captured over the two-year study period. Significant differences were observed in both seasons for several orders, indicating a natural preference towards yellow for taxa such as Diptera (Bekker et al, 2017), Homoptera (Castro et al, 2017), Hymenoptera (Thomson et al, 2004;Gullan and Cranston, 2005) and Thysanoptera (Thomson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sampling methods may result in a strong bias towards certain taxa, highlighting the importance of combining various sampling methods, and three sampling methods (pan traps, bait traps and sweep net) were therefore combined in accordance with the methodology of Castro et al . (). Pan traps and bait traps were deployed along each 90‐m transect in the orchard lanes (under the canopy), during three consecutive days.…”
Section: Methodsmentioning
confidence: 97%
“…Pan and bait traps were checked and cleared of captures daily and the specimens were stored in 70% ethanol. In total, 840 pan traps and 840 bait traps were deployed (for more details, see Castro et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations